2003
DOI: 10.1097/01.wcb.0000058871.46954.2b
|View full text |Cite
|
Sign up to set email alerts
|

The Hemodynamic Impulse Response to a Single Neural Event

Abstract: Summary: This article investigates the relation between stimulus-evoked neural activity and cerebral hemodynamics. Specifically, the hypothesis is tested that hemodynamic responses can be modeled as a linear convolution of experimentally obtained measures of neural activity with a suitable hemodynamic impulse response function. To obtain a range of neural and hemodynamic responses, rat whisker pad was stimulated using brief (Յ2 seconds) electrical stimuli consisting of single pulses (0.3 millisecond, 1.2 mA) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
108
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 130 publications
(116 citation statements)
references
References 45 publications
7
108
0
1
Order By: Relevance
“…For example, Ances et al (2000) found that, taking into account neural nonlinearities, responses to brief stimuli (o4 secs) were linear, while responses to longer stimuli were better explained by a nonlinear model. Similarly, our previous work (Martindale et al, 2003) found the response to brief stimuli to be well modelled by a linear convolution of measured neural activity with a haemodynamic impulse response. An attempt to explain the apparent contradiction between human and animal studies can be found in the discussion.…”
Section: Introductionsupporting
confidence: 65%
See 3 more Smart Citations
“…For example, Ances et al (2000) found that, taking into account neural nonlinearities, responses to brief stimuli (o4 secs) were linear, while responses to longer stimuli were better explained by a nonlinear model. Similarly, our previous work (Martindale et al, 2003) found the response to brief stimuli to be well modelled by a linear convolution of measured neural activity with a haemodynamic impulse response. An attempt to explain the apparent contradiction between human and animal studies can be found in the discussion.…”
Section: Introductionsupporting
confidence: 65%
“…The mean impulse response derived from the 1 to 4 secs stimuli was compared with the flow impulse response previously identified in Martindale et al (2003) (equivalent to equation (2) with d ¼ 2.37 secs, t ¼ 0.76 secs, and C ¼ 10.6). There was a high degree of agreement between the two impulse response estimates (r 2 ¼ 0.96, data not shown), indicating that the responses to the 1 to 4 secs stimuli could be well modelled by the previously identified LCM.…”
Section: Linear Convolution Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Although most of the human fMRI studies employ the event-related task design that has a short stimulus duration, animal studies generally investigate the relationship between BOLD signals and evoked potentials with a stimulus duration of several tens of seconds (Brinker et al, 1999;Van Camp et al, 2006;Goloshevsky et al, 2007;Huttunen et al, 2008;Sanganahalli et al, 2009). Unlike BOLD studies, numerous optical studies performed using laser Doppler flowmetry (LDF) (Ngai et al, 1999;Matsuura and Kanno, 2001;Ureshi et al, 2004Ureshi et al, , 2005 and optical imaging (Devor et al, 2003;Martindale et al, 2003;Sheth et al, 2003Sheth et al, , 2004Jones et al, 2004;Hewson-Stoate et al, 2005;Martin et al, 2006) have investigated the hemodynamic responses such as CBF and deoxygenated hemoglobin changes to neuronal activity in the rat cortex with a short stimulus duration (2-5 s) (Matsuura and Kanno, 2001;Martindale et al, 2003;Sheth et al, 2003Sheth et al, , 2004Jones et al, 2004;Ureshi et al, 2004Ureshi et al, , 2005Hewson-Stoate et al, 2005;Martin et al, 2006). Thus, an animal fMRI study with short stimulus duration is expected to bridge the results of the optical studies using short stimulus durations and those of the BOLD studies using long stimulus durations.…”
mentioning
confidence: 99%